Pengaruh Hasil Investasi, Pendapatan Premi, dan Beban Klaim Terhadap Pertumbuhan Aset pada Asuransi Jiwa yang Terdaftar di Otoritas Jasa Keuangan (OJK) Periode Tahun 2014-2017 - Erlin Nur Setiobekti; Tabrani; Subekti (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2020)
The purpose of this research was to analyze the effect of investment returns, premium income and claims for the growth of assets life insurance at the Financial Services Authority. The population in this research are life insurance companies on the Financial Services Authority at period 2014-2017. The analyze technique used is multiple linier regression.The results of calculations with the F test of 7.168 with growth of assets 0.000 means that simultan investment returns, premium income and claims affect the growth of assets. The results of calculations with the t test of the coefficient of investment returns of -3,294 with a significance level of 0.001 smaller than 0.05 then there is the effect of investment returns on the growth of assets, the value of the premium income coefficient of 4,564 with a significance level of 0,000 less than 0.05 then there is an influence of premium income on the growth of assets, and the claims coefficient value of -3,617 with a significance level of 0,000 less than 0.05, there is an influence of the claims on the growth of assets.